Knowledge of Surveillance Officers on Identification of Healthcare-associated Infections in Surabaya - Anindya Putri Hapsari; Catharina Umbul Wahyuni; Dwiono Mudjianto (Jurnal Berkala Epidemiologi, 2018)
ABSTRACTBackground: The knowledge of nurses in identifying HAIs is required to facilitate surveillance, in addition to applications that facilitate surveillance data collection, one of them is epi info. Haji Hospital has conducted training to increase nurses' knowledge regarding HAIs surveillance. Purpose: This study aims to describe the knowledge of HAIs surveillance officers. Methods: The type research was descriptive observational with cross sectional research design. The research location was in RSU Haji, Surabaya between January-February 2018. The population in the study were all nurses who attended surveillance data collection training. Respondents in this study used total sampling as many as 40 nurses who were representatives of each treatment room. Data were analyzed descriptively. Results: Most nurses have increased knowledge in identifying HAIs, capable to enter data, convert data entries into tables, and change tables into pivot tables in Microsoft Excel after training, and most treatment rooms have applied epi info for data recording HAIs. Conclusion: The implementation of the training was quite effective indicated from the results of the nurse's achievement. This training is expected to be maintained and required a regular monitor the use of epi info, so the training result can sustain and nurses can implement knowledge about HAIs to support the running of HAIs surveillance.